Study on Risk Management in Financing and Operational of Grameen Bank Financing Concept in MBK Finance - Bobby Yulandika Putra (Tazkia Islamic Finance and Business Review, 2013)
Objective – Poverty is one of the most fundamental issues that still surround the life of 29.89 million people of Indonesia (National Statistical Bureau data from January 2, 2012). During this time, the pattern of poverty alleviation programs undertaken by the government is a pattern of generosity. This pattern can directly exacerbate the poor morals and behavior. Ideally, poverty alleviation efforts are made by concrete steps, which empower poor `communities themselves.In line with the theme of this research, one of the financial institutions (non-Banks) who cares and has the spirit to empower people to overcome poverty is Mitra Bisnis Keluarga (MBK). This study aimed to assess the financial risks and operational risks of implementation of Grameen Bank financing concept in MBK.Methods - The method used in this research is literature review and qualitative descriptive study using actual MBK data.Results - Results from this research showed that products with the concept of Grameen Bank financing is relatively safe in the terms of the financing risk, but requires more attention on operational risk and which can be implemented for large-scale poverty alleviation program.Conclusion - The data showed that the risk of financing given to the poor (without collateral) is minimal and MBK actual data shows that the Operational self-sufficiency is relatively high at> 90% Keywords : MBK, Grameen Bank, Poverty